ENHANCING ELEMENTARY STUDENTS' READING COMPREHENSION THROUGH INTERACTIVE STORYTELLING IN ENGLISH LANGUAGE CLASSROOMS: AN INTEGRATIVE REVIEW - Dinda Yarshal; Nurmairina Nurmairina (Sensei International Journal of Education and Linguistic, 2023)
Reading comprehension remains one of the most essential yet challenging skills for elementary students learning English as a foreign language. Many students can recognize words and answer literal questions, but they often experience difficulties in constructing meaning, making inferences, understanding vocabulary in context, and connecting story events with prior knowledge. Conventional reading instruction frequently emphasizes translation, repetition, and factual exercises, while young learners need more interactive, multimodal, and meaningful literacy experiences. This article aims to examine how interactive storytelling can enhance elementary students' reading comprehension in English language learning classrooms. This study employed an integrative literature review by synthesizing international peer-reviewed studies related to storytelling, digital storytelling, multimedia learning, reading comprehension, and English language teaching. The findings indicate that interactive storytelling supports reading comprehension through four main mechanisms: activating prior knowledge, scaffolding vocabulary and narrative structure, promoting inferential thinking, and increasing students' engagement through dialogic participation. The article proposes an Interactive Storytelling Reading Cycle consisting of pre-story engagement, guided story encounter, interactive meaning negotiation, collaborative story reconstruction, and reflective comprehension assessment. The discussion emphasizes that interactive storytelling should not be treated merely as entertainment or digital decoration. Instead, it should be positioned as a structured literacy pedagogy that integrates narrative, interaction, multimodal support, and comprehension strategy instruction. The article concludes that interactive storytelling has strong potential to make English reading instruction more active, contextual, communicative, and developmentally appropriate for elementary learners.